Shock, Chaos, and Change: An Elementary School Turned Upside Down. (June 2016) - Cantú, Yvette; Rocha, Patricia; Martinez, Melissa A.
The following case is inspired by real-life events that the authors experienced while working in the K-12 public school system. This case describes the experiences of Mrs. Hodge, a seasoned assistant principal who was unexpectedly assigned to be principal of her elementary school. The case follows Mrs. Hodge through her first 3 years as the principal of Thomas Elementary and describes the challenges she faced as her relationships with teachers changed, the school experienced high teacher turnover, and academic achievement among students declined.